Labour Market Reforms and Unemployment: Lessons from the Experience of the OECD Countries - Stefano Scarpetta (Inter-American Development Bank, Office of the Chief Economist, 1998)
The OECD labor market has undergone major changes over the past two decades. The most evident of these changes is the rise in the number of job-seekers. In 1997, there were more than 35 million people unemployed in the OECD area as a whole, some 6 million more than in the mid-1980s and almost 25 million more than in the early 1970s. These figures hide profound differences across countries. In the major European countries, unemployment has increased dramatically over the past two decades and in some of them, including Italy, Spain, and France, increases that were initially cyclical have tended to become structural over time.
Keywords: 330; Arbeitsmarkt; Reform; Arbeitsmarktpolitik; Arbeitslosigkeit; OECD-Staaten